The Effect of Age, Smoking and Exercise on Sorbitol Dehydrogenase and its Correlation Factor with Some Biochemical Variables in Diabetics - Wasan Ali; Maher Al - Dabbagh (College of Education for Pure Sciences, 2013)
ABSTRACT      This research includes a biochemical study of sorbitol dehydrogenase (SDH) in the serum of the control and patient with diabetes mellitus. Their ages ranged between (8-65year) . It has been shown that the mean value of (SDH) activity is (0.015± 0.010) of the control group and )0.516±0917) of the patient groups .The result shown that significant increase in activiyof (SDH) patient groups and for each sexes when compared with control groups .There was a study of the relationship between (SDH) activity and clinical variables of the control and patient groups by finding the linear correlation was studied. Moreover , there was positive significant correlation between the activity of enzyme and each of glucose , total protein , albumin , globulin , in control and patient groups . Inverse significant correlation between the activity and Ca++ in control and patient groups .